O uso do simulador Mozaik3D como ferramenta para o ensino do campo eletromagnético da terra - CARDOSO, Derik Alan Oliveira (2024)
One of the challenges faced by high school students is understanding the physical concepts of Earth’s electromagnetism, which are often represented by abstract quantities that are difficult to visualize. To address this issue, this project was developed, proposing a teaching methodology based on the use of a software called Mozaik3D. This software allows students to observe and analyze the definitions of the Earth’s electromagnetic field and its importance for life on Earth. Based on Lev Vygotsky’s “Socio-Interactionist Theory” and David Ausubel’s “Meaningful Learning,” a methodology was developed for better application of the project, using questionnaires before and after implementation to evaluate the effectiveness of the employed methodology. It was applied to three classes of the third year, totaling 60 students. We obtained satisfactory results: in the first questionnaire, we had only 10% correct answers, while in the second questionnaire, we achieved 80% correct answers. The objective of this work is to present the achieved results, methodology, and verify if these approaches contributed to increasing students’ interest and learning in physics, as well as to the development of skills such as creativity, logical reasoning, and critical thinking. The simulator is available for free on the internet and can be downloaded on smartphones, tablets, and computers. These devices can be effective tools for instant research and access to diverse educational applications, enriching the learning environment. However, it is crucial to balance their use to avoid distractions and ensure a focused and productive educational environment. Thus, the project proposes a more interactive and audiovisual way to stimulate students’ pursuit of knowledge.